Analysis of electroencephalogram (EEG) signal from dyslexic children using Coiflet / Muhammad Firdaus Mohd Yusof - Mohd Yusof, Muhammad Firdaus (2016)
The usage of statistic over the set of feature is one of possible method to identify differences in the brain electrophysiological processing for dyslexic children. Dyslexia is one of neurological disorder related to the brain causing learning deficiencies especially on reading although research has proved that writing problem also contribute significant challenge into this issues. This study looks into the analysis of electroencephalogram (EEG) signals during writing and resting activities for poor dyslexic, capable dyslexic and normal children using Coiflet. C3, C4, FC5, FC6, P3, P4, T7 and T8 are the eight electrodes position known as the pathway for writing and reading. The result shows that there are significant differences in the minimum and maximum of the extracted features for dyslexic category using Coiflet.